Pesquisas no campo da didática : subsídios ao ensino e à aprendizagem de conteúdos e desenvolvimento de habilidades e competências - Moreira, Raquel (Universidade Federal de São Carlos, 2017)
Considering the Brazilian education's fragility, expressed in the low scores of students in national and international standardized tests, and considering the current context of the information society, in which mastering knowledge in the instrumental dimension is key for either providing opportunities or deepening exclusion situations, the present thesis aims to analyze and systematize evidences of instruments that Brazilian research in the field of Didactics, available in SciELO database between the years 2000 and 2015, have been offering to the development of content, abilities and competences to school practices. The investigation was based on bibliographic research, using mixed methods, supported by Content Analysis of Laurence Bardin, and was guided by the question: What has the knowledge produced in the field of Didactics, available in SciELO between the years 2000 and 2015, been offering as instruments to the development of the process of teaching and learning of contents, abilities and competences in Basic Education? The main results indicate that, from the 119 articles referring to Basic Education, pertaining to 11 (eleven) areas of knowledge, and in different teaching stages and modalities, it was possible to identify 26 (twenty-six) registry units (RU). The most frequent RU were: content teaching; teaching materials and teaching materials analysis; teaching and learning; analysis of teacher practice, teaching practices, interaction, and teaching. All of the RU carry correlations of theoretical, methodological/procedural and material dimensions, enabling to affirm that the descriptor “Didactics” has been used in articles that are, indeed, dedicated to important elements of the area. However, one or another element is focused in exclusive manner, detaching dimensions of the teaching and learning process, or detaching class processes from the consequences generated to students' learning. Therefore, it is necessary to undertake, in the area, research procedures that expand the contributing potential in order to improve teaching quality by teachers, and improve learning outcomes of students.
Keywords: Didática; Conhecimento científico; Ensino e aprendizagem; Conteúdos; Habilidades; Competências; Didactics; Teaching and learning; CIENCIAS HUMANAS::EDUCACAO::CURRICULO; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM